A Sociological Study of Conversions in Kazakhstan - AYDINALP, HALİL (My University, 2021)
Kazakh society went through such policies as Russification and Christianization during the Russian occupation period, atheism during the Soviets period, and religious revival after its independence. After the independence, missionary work of the Christian religion along with Islam increased. As a result of the missionary activities that are increasing today, Kazakhs who have changed their religion have started to appear in the society. This research explores the Kazakhs who changed their religion as a result of the intensive missionary work that emerged after independence from a sociological perspective. Then, the qualitative research method of sociology was used to investigate the current and complex events of religious change. There are three (complementary) techniques that we have used in qualitative research. They are: Interview, document examination and observation. In our research, 25 individuals were interviewed and personal information about them was provided. The process of changing religion and the reasons they changed religion were examined.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; İlahiyat; Social Sciences and Humanities; Sociology; Theology; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; DİN; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; RELIGION; General Social Sciences; Religious Studies; Social Sciences & Humanities; Kazakhstan; Conversion; Christianization; Missionary; Sociology of religion; Social change.